Influence of alkali activator concentration on synthesis of high calcium fly ash geopolymer. - a/l Malaichelvan, Arevind Chelvan (IRC, 2016)
Concrete made from Portland cement has started to show signs of degradation under corrosive environment. A greener alternative to Portland cement is synthetic geopolymer cement which also exhibits better physical characteristics than Portland cement. This research work focuses on manufacturing high calcium fly ash based geopolymer concrete and also to identify the effects of alkali activators on the properties of high calcium fly ash based geopolymer concrete. Through this, the short term engineering properties off fresh and hardened high calcium fly ash based geopolymer concrete was studied.